Notable gray fox (Urocyon cinereoargenteus) record in southern México City - Hernández-Romero, Pablo César; Prieto-Torres, David Alexander; Botello, Francisco; Muench-Spitzer, Carlos E. (Therya Notes, 2024)
The study of wildlife in cities and their urbanized areas of influence is essential for long-term conservation. The presence of wild mammals in natural vegetation patches and urban parks of México City (CDMX) was evaluated to determine the current state of wild mammals in the area. Twenty camera-trap stations were placed to record wild mammals inhabiting green areas in southern México City as part of the project "Mammal Diversity in Modified Landscapes of southern México City: Importance of Green Areas and Connectivity in Urban Contexts". Gray foxes were only recorded in Bosque de Tlalpan. A total of 38 photographic records of the gray fox (Urocyon cinereoargenteus) were captured at 2 sites in Bosque de Tlalpan. These records were obtained from August 5, 2021 to March 29, 2022. The period of activity of this species was mainly nocturnal, with records from 22:00 hr to 01:00 hr. The new records of gray foxes in southern México City are relevant because they show that, despite the high degree of fragmentation of the green areas within the city, there are still medium-sized wild carnivorous mammals inhabiting these patches. These records are crucial for understanding the degree of connectivity between green areas in the south of the city.